Exploring Intercultural Awareness among Moroccan EFL Pre-service Teachers - Mouhssine Echcharfy (Journal of English Language Teaching and Linguistics, 2022)
With the status of English as a lingua franca and the high social mobility, one of the current goals of pre-service teacher training programs consists in preparing intercultural competent practitioners who are capable of teaching learners how to communicate effectively and appropriately in cross-cultural encounters. Thus, the scarcity of intercultural courses in such training programs may represent a serious challenge for them. In light of this, the present paper intends to explore Moroccan pre-service EFL teachers’ intercultural awareness. In view of Byram’s (1997) Model of intercultural competence, a three-point Likert scale questionnaire and a semi-structured interview were adopted. In consideration of a convenience sampling, the study included ninety (n=90) trainee teachers from different TEFL/TESOL programs and pre-service teacher training centers in Morocco. The findings revealed that pre-service EFL teachers exhibit desirable attitudes towards cultural diversity. Nevertheless, it was observed that the participants’ knowledge about the Moroccan and the American cultures is shallow. It also turned out that pre-service teachers’ lack the mediation skills, including critical cultural awareness that an intercultural speaker/intermediary needs in intercultural encounters. The study addresses several implications regarding teacher education.